The Influence of Impulse Buying and Hedonic Consumption in The Viral Fashion Skena Trend on TikTok on Gen-Z Overspending - Dita Wulandari Agustin; Rizki Febri Eka Pradani (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
This study aims to analyze the influence of impulse buying and hedonic consumption in the viral fashion skena trend on TikTok on Generation Z overspending. The development of the TikTok social media platform has created a new consumption ecosystem that encourages unplanned purchasing behavior, especially among Generation Z who are the dominant users of the platform. This study uses a quantitative method with an associative approach. Sampling was carried out using a purposive sampling technique with a total of 400 Generation Z respondents in East Java who are aware of and directly exposed to the fashion skena trend on TikTok and have purchased fashion products inspired by the viral content. The research instrument was a questionnaire with a Likert scale of 1-4 that has been tested for validity and reliability. Data analysis used multiple linear regression with the help of SPSS software. The results of the study indicate that simultaneously, impulse buying and hedonic consumption have a positive and significant effect on Generation Z overspending in the viral fashion skena trend on TikTok. These findings indicate that the higher the tendency of impulse buying and hedonic consumption triggered by viral fashion content on TikTok, the higher the overspending behavior among Generation Z. This research is expected to contribute to the development of financial literacy and serve as a reference for further research related to digital consumer behavior in the social media era. Keywords: Impulse Buying, Hedonic Consumption, Skena Fashion on TikTok, Overspending, Generation Z.